Exosome therapeutics for lung regenerative medicine. Issue 1 (29th June 2020) - Popowski, Kristen; Lutz, Halle; Hu, Shiqi; George, Arianna; Dinh, Phuong‐Uyen; Cheng, Ke
ABSTRACT: Exosomes are 30 to 100 nm extracellular vesicles that are secreted by many cell types. Initially viewed as cellular garbage with no biological functions, exosomes are now recognized for their therapeutic potential and used in regenerative medicine. Cell‐derived exosomes are released into almost all biological fluids, making them abundant and accessible vesicles for a variety of diseases. These naturally occurring nanoparticles have a wide range of applications including drug delivery and regenerative medicine. Exosomes sourced from a specific tissue have been proven to provide greater therapeutic effects to their native tissue, expanding exosome sources beyond traditional cell lines such as mesenchymal stem cells. However, standardizing production and passing regulations remain obstacles, due to variations in methods and quantification techniques across studies. Additionally, obtaining pure exosomes at sufficient quantities remains difficult due to the heterogeneity of exosomes. In this review, we will underline the uses of exosomes as a therapy and their roles in lung regenerative medicine, as well as current challenges in exosome therapies.